2021
DOI: 10.3390/computers10040046
|View full text |Cite
|
Sign up to set email alerts
|

Improving Response Time for Crowd Management in Hajj

Abstract: Flying Adhoc Network (FANET) is a particular type of Mobile Adhoc Network (MANET) that consists of flying drones or unmanned aerial vehicles (UAVs). MANETs are especially useful in rural and remote areas, where the lack of public networks necessitates data delivery through mobile nodes. Additionally, FANETs provide better coverage where there is a lack of roads. Generally, the goal of FANETs is to provide multimedia data to applications such as search and rescue operations, forest fire detection, surveillance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 23 publications
(21 reference statements)
0
14
0
Order By: Relevance
“…Similarly, intelligent shelter allotment (ISA) [111] was suggested to optimize the evacuation activities and define the best routes and shelter locations. Priority-based Routing Framework for Flying Adhoc Networks (PRoFFAN) is recently suggested for expediting the delivery of critical image data to control centers in case of natural disasters [112]. Hajj Gear is another proposed system that allows pilgrims to press an SOS button that they have in their wearable sensor in case of an emergency.…”
Section: Disasters and Emergenciesmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, intelligent shelter allotment (ISA) [111] was suggested to optimize the evacuation activities and define the best routes and shelter locations. Priority-based Routing Framework for Flying Adhoc Networks (PRoFFAN) is recently suggested for expediting the delivery of critical image data to control centers in case of natural disasters [112]. Hajj Gear is another proposed system that allows pilgrims to press an SOS button that they have in their wearable sensor in case of an emergency.…”
Section: Disasters and Emergenciesmentioning
confidence: 99%
“…ICT was used in planning various aspects of Hajj and Umrah as well. For instance, Deep Learning (DL) was used to estimate the number of pilgrims visiting the holy sites in Technology References Ad-Hoc Networks [80], [112] Adrouino Microcontroller [70], [190], [287] Augmented Reality (AR)-Virtual Reality (VR)-Mixed Reality (MR) [93], [133]- [138], [140], [144], [146], [207], [211] Business Intelligence (BI) [42], [183] Big Data Analytics [50], [169] Bluetooth Low Energy (BLE) [68], [115], [191], [238]- [241], [288] Blockchain [154], [155], [162], [289]-[291] Closed-Circuit TeleVision (CCTV) [248], [292] Cellular Networks [70], [71], [81], [107], [115], [187], [189], [191], [196] Cloud Computing [75], [220], [229], [267], [293], [294] Cryptography…”
Section: Infrastructure and Planningmentioning
confidence: 99%
“…In contrast to similar work in [72], the authors in [31] have employed cloud computing to perform resource-intensive pose estimation tasks, allowing the system to be implemented in real-time applications. Authors in [73] have proposed a priority-based routing framework for flying adhoc networks (PRoFFAN) for better data delivery to decision and control centers. They have found that the PRoFFAN has improved the response time of the flying adhoc network (FANET) application.…”
Section: Crowd Analysesmentioning
confidence: 99%
“…Many researchers have studied crowded events and have contributed towards the improvement of their management. A good account of crowd management can be found in [19][20][21][22]. In particular, in [20], the authors present a framework for crowd management, which was implemented in the case of the annual Hajj pilgrimage.…”
Section: Literature Reviewmentioning
confidence: 99%